2016
DOI: 10.1136/bmjopen-2016-013885
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable diseases in decontamination workers in areas affected by the Fukushima nuclear disaster: a retrospective observational study

Abstract: ObjectivesTo assess the prevalence of non-communicable diseases (NCDs), and whether NCDs were treated or not, among hospitalised decontamination workers who moved to radio-contaminated areas after Japan's 2011 Fukushima Daiichi Nuclear Power Plant disaster.MethodsWe retrospectively extracted records of decontamination workers admitted to Minamisoma Municipal General Hospital between 1 June 2012 and 31 August 2015, from hospital records. We investigated the incidence of underlying NCDs such as hypertension, dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Sawano et al . have pointed out a high prevalence of lifestyle-related diseases, such as dyslipidemia, diabetes mellitus, and hypertension, in hospitalized decontamination workers 9) . A casual lifestyle might increase the risk of exertional heat illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sawano et al . have pointed out a high prevalence of lifestyle-related diseases, such as dyslipidemia, diabetes mellitus, and hypertension, in hospitalized decontamination workers 9) . A casual lifestyle might increase the risk of exertional heat illness.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation 4,5) and excessive alcohol consumption 6,7) were risk factors for heat illness; however, most of the workers were temporary employees and their lifestyle, in general, was casual 8) . Sawano 9) . A casual lifestyle might increase the risk of exertional heat illness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported high rates of alcohol consumption and smoking among decontamination workers following the FDNPP accident (Sawano et al, 2016b). After the Chernobyl accident, workers engaged in clean-up work in Estonia were also reported to be significantly more susceptible to issues with alcohol (Laidra et al, 2015).…”
Section: Alcohol Drinking and Smokingmentioning
confidence: 96%
“…A considerable proportion of the decontamination workers are hired from other parts of Japan due to a severe shortage of workers in Fukushima, and almost all of these migrant workers live in workers' dormitories or shared houses, thereby sharing spaces with each other; our case experienced these same circumstances. Poor living conditions are reported to be a possible cause for the high burden of non-communicable diseases (NCDs) among the decontamination workers 17) .…”
Section: Case Presentationmentioning
confidence: 99%